التقييم السياحي للموارد الطبيعية في منطقة الحفة ـ محافظة اللاذقية - خضرة جلال بدر (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تعتبر الموارد الطبيعية المتوافرة في منطقة ما نقطة البداية والأساس لتطوير صناعة السياحة وبالتالي للنهوض بمستوى المنطقة اقتصادياً وخدمياً واجتماعياً. ولإظهار إمكانيات أي منطقة سياحياً لابد من إجراء تقييم سياحي لمواردها الطبيعية، من هنا جاءت أهمية هذا البحث الذي تناول موضوع إجراء تقييم سياحي للموارد الطبيعية في منطقة الحفة التي تتميز بفرادة مواردها وتميزها على مستوى المحافظة وتم إجراء التقييم بالاستعانة ببرنامج GIS للوصول إلى النتائج المرجوه. The natural resources that are available in a region are considered to be the starting point and the basis for the development of the tourism industry and this for the region advancement this economically and service and socially, and to show the potentials of any area touristically we must perform a touring assessment of its natural resources, from here came the importance of this research which dealt with performing a touring assessment of natural resources in Alhaffeh area that is characterized by uniqueness of its resources and excellence at the province level, the assessment was performed using GIS program to reach the desired results.